Comparison of Emotion-Focused Therapy and Acceptance and Commitment Therapy on Quality of Life, Pain Perception, and Trunk Muscle Endurance in Women with Hand Osteoarthritis - Moghadasi, Sara; Rafiepoor, Amin (Psychology of Woman Journal, 2025)
Objective: The present study aimed to compare the effects of Emotion-Focused Therapy (EFT) and Acceptance and Commitment Therapy (ACT) on quality of life, pain perception, and trunk muscle endurance in women with hand osteoarthritis. Methods and Materials: This research employed a quasi-experimental design with pretest, posttest, follow-up stages, and a control group, with a follow-up period of three months. The research population consisted of all women diagnosed with hand osteoarthritis during 2024–2025. A total of 45 individuals were selected from the research population using purposive sampling and randomly assigned to experimental and control groups (15 participants in each group). Data were collected using the World Health Organization Quality of Life Questionnaire, the Melzack Pain Perception Questionnaire (Melzack, 1975), and a trunk muscle endurance test. Participants in the experimental groups received either Emotion-Focused Therapy over 12 sessions or Acceptance and Commitment Therapy over 8 sessions; the control group did not receive any therapeutic intervention. Data analysis was conducted using mixed-design repeated measures analysis. Findings: The results showed that, after controlling for the pretest effects, there were significant differences between the experimental and control groups in the posttest scores of quality of life, pain perception, and trunk muscle endurance at the 0.05 significance level (p < .05). Moreover, the findings indicated that there were differences between Emotion-Focused Therapy and Acceptance and Commitment Therapy in their effects on quality of life, pain perception, and trunk muscle endurance in women with hand osteoarthritis. Conclusion: It can be concluded that Emotion-Focused Therapy and Acceptance and Commitment Therapy differently impact quality of life, pain perception, and trunk muscle endurance in women with hand osteoarthritis.